Trial of CGA-72662 (Larvadex) as a feed additive for controlling flies breeding in caged chicken manure - Fadzil, M.; Hamid, Ramlah; Ragawan, K. (Persatuan Doktor Veterinar Malaysia, 1987)
CGA-72662 (LARVADEX) was tried as a feed additive for controlling flies breeding in poultry manure. At 5 ppm it was able to completely suppress development of fly larvae in 45 days of feeding onwards and continued to be effective for about 25 days post withdrawal of the medicated feed. An increase in egg production was observed when LAR VADEX was added to the feed. There was also an improvement in feed efficiency